Geoelectric Studies in Controlled Landfill in the Municipality of Caçapava do Sul - RS - Santos, Ana Carolina Oliveira dos; Kamphorst, Juliana de Souza Corrêa; Mello, Fernanda Vargas de; Moreira, César Augusto (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The application of geophysical methods in environmental studies, primarily in the characterization and monitoring of contaminated areas, is facing increasing demand for new techniques in environmental research due to the imminent risk that the population is subject depending on the Pollution of soil, groundwater and possible scarcity of drinking water. The presence of contaminants in the environment can change its properties in a range of variation often can be detected by geophysics. Thus, this study presents the results of application of geophysical methods of resistivity and spontaneous potential, using the technique of electrical profiling, in an area of waste disposal, in order to detect anomalous zones to physical parameters that can be associated with contamination from the decomposition of waste. The study demonstrated the effectiveness of geophysical methods to detect zones of preferential flow, direction of groundwater flow in the area of waste disposal and the occurrence of intervals contaminated.